MANFAAT PERSONAL BRANDING & PROFESSIONAL NETWORKING UNTUK HIRING DECISION PADA MEDIA LINKEDIN BAGI PERUSAHAAN - Edy Chandra (STIA MALANG, 2023)
Most of the large companies in Indonesia have implemented online recruitment as a recruitment methodbecause it is considered to save costs, time and effort in the recruitment process. This study uses descriptivedata types collected through documents available on the linkedin web, companies and users or applicants.To ensure that the data is appropriate as REQUIRED, triangulation is carried out, to test the validity of thedata by utilizing the sources, methods, investigators, and theories used. The results of this study prove thatappropriate personal branding, professional networking and professional networking provide benefits forapplicants and companies in recruitment. For companies, if the data and information listed by applicantson LinkedIn is not appropriate, then the purpose of online recruitment has not provided optimal results,saving costs, time and effort in the recruitment process. So the company needs to be observant in seeingand knowing the applicant's information and the applicant must present complete and up to dateinformation. So companies must improve the screening process in the recruitment process with LinkedInmedia by utilizing the tools provided by LinkedIn to simplify the recruitment process, and be able to searchfor and find the prospective employees needed to improve effective hiring decisions